Influence of Environmental Factors on the Surface Feeding Behaviour of Immature Male Whale Sharks in the Gulf of Tadjoura (Djibouti) - Francesca Romana Reinero; Andrea Marsella; Antonio Pacifico; Consuelo Vicariotto; Lara Maule; Makenna Mahrer; Primo Micarelli (Conservation)
The East African country of Djibouti is known to host an important seasonal feeding aggregation of whale sharks that allows the frequent observation of their surface feeding behaviour. The influence of environmental factors on the different whale shark feeding strategies (passive, active, and vertical) was studied over a four-year period (2017, 2020, 2022, 2024) in the Gulf of Tadjoura. Across 81 immature male whale sharks identified and 1082 surface feeding behaviours recorded in this period, the chlorophyll-a concentration was the main parameter predicting the choice of the filter-feeding technique. Active and vertical feeding behaviours were associated with rainfall, lower sea surface temperature, worse sea conditions, and low wind speed during the morning, all factors positively correlated to chlorophyll-a concentration. On the contrary, passive feeding behaviour was favoured in the inverse environmental conditions. Both passive and vertical feeding behaviours occurred during El Niño events, whereas active feeding was more common during La Niña events. Since it is known that whale shark abundance and distribution are associated with food availability at coastal locations, it is fundamental to understand environmental drivers of filter-feeding strategies when managing conservation efforts for this endangered species. Recommendations for future research work at this site are presented.